An Outbreak of Invasive Group A Streptococcal Infections in Injection Drug Users. (4th October 2017) - Gittzus, Jennifer; White, Joshua; Caine, Lynda; Hansen, Katrina; Daly, Elizabeth; Chan, Benjamin; Bowen, Hannah; Metcalf, Erin; Pierce, Lindsay; Kusch, Rachel; Benton, Christopher; Gao, Fenxiang; et al.
Abstract: Background: Opioid addiction is a major public health problem, and New Hampshire has the second highest overdose death rate in the nation (34.3 deaths per 100, 000 population in 2015). In October 2016, the Infectious Disease (ID) service at an acute care hospital in central New Hampshire was consulted on 4 cases of S. pyogenes a.k.a. Group A Streptococcal (GAS) septicemia in injection drug users (IDUs) within less than a week. The cluster was reported to the NH Division of Public Health Services (DPHS) and an outbreak investigation was begun. Methods: Additional case finding was instituted by signage in areas of at-risk populations, press releases, and a statewide health alert network (HAN) bulletin to clinicians. DPHS interviewed possible cases using a standardized questionnaire, and cases of invasive GAS reported in the previous 3 months were reviewed. The initial 4 isolates were collected for pulsed-field gel electrophoresis (PFGE) and whole genome sequencing (WGS). Results: A total of 11 cases of invasive GAS infection in IDUs were identified, 82% of which occurred within the month of October. The most common associated diagnosis was septicemia (90%), followed by cellulitis (67%), sepsis (55%), and pneumonia (18%). Ten (90%) patients were also co-infected with hepatitis C and a majority (55%) were homeless. Three-quarters of the initial cases had identical isolates by PFGE and WGS. Two of these individuals were found to have a social connection. Of the 4 sentinel cases, all completed 10 days of parenteral antibiotics with clinical improvement. However, long-term outcomes were poor, largely due to sequelae of substance addiction. Conclusion: An invasive GAS outbreak was identified in a cluster of IDUs and associated with homelessness, with a majority presenting with septicemia or sepsis. Close cooperation between local clinicians and DPHS was crucial to identifying and determining the scope of this outbreak. GAS is not a well-known but life-threatening pathogen in IDUs, and clinicians need increased awareness, especially during an outbreak. Disclosures: All authors: No reported disclosures.